Wadah Aneuk Muda Sebagai Nara Hubung Pendidikan Kesehatan Reproduksi Remaja Di SMA Negeri 5 Kota Lhokseumawe Tahun 2024 - Yenni Fitri Wahyuni; Aida Fitrani; Nova Sumaini Prihatin; Ika Friscila (Jurnal Pengabdian Bidang Kesehatan, 2024)
Adolescence is a period of rapid growth and development, both physically, psychologically and intellectually. Cases of early marriage are increasing not only outside Aceh, cases of early marriage also occur in the area nicknamed Serambi Mekah. The purpose of the activity is to provide counseling to adolescents about Adolescent Reproductive Health, to increase the use of the young aneuk container as a liaison for reproductive health at SMA Negeri 5 Lhokseumawe City. The implementation of this community service activity lasted 2 days, namely the first day began with a pre-test followed by material filling and role play, the second day continued with material filling and the formation of the PIK-R adolescent counselor team and a Post-test knowledge evaluation. The results obtained increased knowledge in respondents about knowledge of Drugs and Reproductive Health, in the pre-test evaluation the target who had good knowledge about Drugs amounted to 4%, in the Post-test evaluation increased to 7%. And the results of the pre-test respondents who had good knowledge about adolescent reproductive health education amounted to 5%, in the post-test evaluation increased to 8%. It is hoped that adolescents can form peer counselors and provide education to peers about reproductive health education, and this activity can be continued accompanied by teachers.